Key trends in morbidity and mortality rate due to ovarian cancer in Ukraine - Romaniv, M.; Terenda, N. (Journal of Education, Health and Sport, 2023)
Introduction. Ovarian cancer is characterized by the unfavorable progression and is in the first place within the structure of women’s mortality rate due to oncogynecological disorders. The purpose is to conduct the comparative analysis of the morbidity and mortality rate due to ovarian cancer before COVID-19 pandemic and during quarantine measures. Materials and methods. We conducted the analysis based on the statistical data from the National Cancer Register of Ukraine 2015 to 2021 without temporarily occupied territories using the statistical method, that is, analysis of time series. We analyzed the morbidity and mortality rate, distribution by age, structure of detection stages for ovarian cancer by TNM classification, detection rate of patients with ovarian cancer during preventive examinations. Research results and their discussion Long quarantine measures caused by COVID-19 pandemic have led to the broken communication between female patients and doctors within the primary and special medical assistance: limited possibility or full impossibility of getting a consultation by the general practitioner/family doctor due to a large number of COVID-19 patients, limited access to specialized healthcare institutions, personal fear of female patients to catch COVID-19 in healthcare institutions. These conditions have made women postpone their visits to doctors and a share of female patients with oncogynecological disorders detected at the stage ІІІ to IV by TNM classification increase. 2015 to 2019 there was a trend in decrease in the share of patients with ovarian cancer detected during preventive examinations by 19.7 %, which increased during quarantine measures due to COVID-19 pandemic (-27.4 %). 2015 to 2019 there was a stated trend in decrease in the share of detected patients with ovarian cancer at the stage I to II (-1.4 %) and III (-9.3 %) by TNM classification and increase in the share of detected patients with ovarian cancer at the stage IV (+17.2 %). During quarantine measures the share of patients with ovarian cancer at the stage I to II and III by TNM classification continued to decrease (-10.3 % and -0.7 %, respectively) and the share of patients with ovarian cancer at the stage IV increased (+20.4 %). The decrease in the share of detected patients with ovarian cancer during preventive examinations is one of the factors for detecting patients with the extensive-stage disease, which was confirmed both at the national and regional level. Conclusion. Obtained data are evidence of the fact that the morbidity rate due to ovarian cancer insignificantly increased (+3.9 %) 2015 to 2019 and decreased by 8.6 % during COVID-19 pandemic. The morbidity rate increased among women aged from 45, especially at the age 65 to 69. The decrease in the share of detected patients with ovarian cancer during preventive examinations is one of the factors for detecting patients with the extensive-stage disease, which was confirmed both at the national and regional level.